Propionate Induces Virulent Properties of Crohn’s Disease-Associated Escherichia coli - Pobeguts, Olga V.; Ladygina, Valentina G.; Evsyutina, Daria V.; Eremeev, Artem V.; Zubov, Aleksandr I.; Matyushkina, Daria S.; Scherbakov, Peter L.; Rakitina, Daria V.; Fisunov, Gleb Y. (Frontiers in Microbiology, 2020)
Crohn’s disease (CD) is a severe chronic immune-mediated granulomatous inflammatory disease of the gastrointestinal tract. The mechanisms of CD pathogenesis remain obscure. Metagenomic analysis of samples from CD patients revealed that several of them have the elevated level of Escherichia coli with adhesive-invasive phenotype (AIEC). Previously we isolated an E. coli strain CD isolate ZvL2 from a patient with CD, which features AIEC phenotype. Here we demonstrate that prolonged growth on propionate containing medium stimulates virulent properties of CD isolate ZvL2, while prolonged growth on glucose reduces these properties to levels indistinguishable from laboratory strain K-12 MG1655. Propionate presence also boosts the ability of CD isolate ZvL2 to penetrate and colonize macrophages. The effect of propionate is reversible, re-passaging of CD-isolate on M9 medium supplemented with glucose leads to the loss of its virulent properties. Proteome analysis of CD isolate ZvL2 growth in medium supplemented with propionate or glucose revealed that propionate induces expression porins OmpA and OmpW, transcription factors PhoP, OmpR and universal stress protein UspE, which were previously found to be important for macrophage colonization by enteropathogenic bacteria.